No such thing as ghosts - Vernon, Ursula (Vernon, Ursula. Dragonbreath, 2011)
Not only must Danny and Wendell trick-or-treat with skeptical classmate Christiana, school bully Big Eddy dares them to enter a haunted house on Halloween night, where they may have to sacrifice their candy to a ghost.